Background for the Development of Gastronomy Enterprises in Knowledge-Based Economy - Gheribi, Edyta; Majda, Aleksandra (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The development of gastronomy enterprises is important because in today's world food and beverage companies play an important role in satisfying the changing nutritional needs of consumers. The development of the food service market undoubtedly is related to the social and economic changes taking place in recent years in our country. Once the industrial economy has turned into knowledge-based economy there are not only material assets but also intellectual resources that decide whether a company is able to earn and maintain competitive advantages or not.